2017
DOI: 10.3390/met7070254
|View full text |Cite
|
Sign up to set email alerts
|

On the Short Surface Fatigue Crack Growth Behavior in a Fine-Grained WC-Co Cemented Carbide

Abstract: Abstract:In the present study, the fatigue crack growth (FCG) behavior of short surface cracks in a fine-grained cemented carbide with a length of less than 1 mm was investigated. The rotating bending and the four-point bending fatigue tests were carried out at stress ratios of R = −1 and R = 0.1 (R = maximum stress/minimum stress). It was found that a short surface crack had a longer stable fatigue crack growth area than a long through-thickness crack; the FCG behaviors of the two types of crack are clearly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…On the one hand, fractographic analysis has been used for invoking correlations between fatigue life and the size of microstructural defects on the basis of Murakami's geometrical parameter of maximum flaw area [17][18][19]. On the other hand, notched specimens have been used for assessing microstructural effects on fatigue response under service-like conditions, e.g., presence of stress concentrators in component geometry as crack starting points and exposure to high temperatures [17,[20][21][22][23]. Tarragó and coworkers [13,15,16] have implemented the above protocol in several microstructurally different cemented carbides in terms of the binder chemical nature (either Co or Ni or CoNi) and content (between 10 and 15 wt%), as well as carbide grain size (between 0.4 and 2.4 µm).…”
Section: Fatigue Mechanicsmentioning
confidence: 99%
“…On the one hand, fractographic analysis has been used for invoking correlations between fatigue life and the size of microstructural defects on the basis of Murakami's geometrical parameter of maximum flaw area [17][18][19]. On the other hand, notched specimens have been used for assessing microstructural effects on fatigue response under service-like conditions, e.g., presence of stress concentrators in component geometry as crack starting points and exposure to high temperatures [17,[20][21][22][23]. Tarragó and coworkers [13,15,16] have implemented the above protocol in several microstructurally different cemented carbides in terms of the binder chemical nature (either Co or Ni or CoNi) and content (between 10 and 15 wt%), as well as carbide grain size (between 0.4 and 2.4 µm).…”
Section: Fatigue Mechanicsmentioning
confidence: 99%
“…Therefore, as compared with the short-surface cracks, the long through cracks are highly susceptible to K max and ∆K [6], and shows FCG characteristics of brittle materials such as ceramics.…”
Section: Comparison With the Fcg Behaviour Of Long Through Cracksmentioning
confidence: 99%
“…Ishihara et al [5] reported the FCG characteristics of the short surface crack at various stress ratios using the cemented carbide with comparatively large WC grain size. Mikado et al [6] studied the FCG behavior of the short surface crack at stress ratio, R = −1 using the finegrained cemented carbide.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for failure is that, under the simultaneous action of mechanical stress and thermal stress, microcracks are formed and then propagate until the failure of the cemented carbide tools occurs [4,5]. Mikado et al [6] investigated the fatigue crack growth (FCG) behavior of short surface cracks in a fine-grained cemented carbide with a length of less than 1 mm and found that the FCG was along the brittle WC/WC interface in a low maximum stress intensity factor. Wu et al [7] conducted experiment on direct micro milling of cemented carbide with a polycrystalline diamond (PCD) micro end mill, whose research suggested that the tool wear process presented microchipping on the cutting edge and exfoliating on the rake face in the early stage, and then presented severe abrasive and adhesive wear on the bottom face in the following stage.…”
Section: Introductionmentioning
confidence: 99%